Exploring the impact of robot interaction on learning engagement: a comparative study of two multi-modal robots - Ka Yan Fung; Kwong Chiu Fung; Tze Leung Rick Lui; Kuen Fung Sin; Lik Hang Lee; Huamin Qu; Shenghui Song (Smart Learning Environments)
Abstract In recent years, there has been a growing interest in using robots within educational environments due to their potential to augment student engagement and motivation. However, current research has not adequately addressed the effectiveness of these robots in facilitating inclusive learning for diverse student populations, particularly those with dyslexia. This study proposes an inclusive learning system developed on two multi-modal robots, Kebbi and Minibo, with interactive (i.e., movable hands) and straightforward features. The system integrates various interactive elements, such as animations, songs, dance, gestures, and touch, to enhance students’ learning engagement, interaction, and motivation and cater to their diverse needs. The study aims to examine the influence of different features from two unique multi-modal robots on the engagement levels of students with/without dyslexia and their needs when engaging with robot learning. Two research questions are posed: (1) What are the features of multi-modal robots that could effectively improve the learning engagements of students with/without dyslexia? (2) What are the needs of students with/without dyslexia when engaging with robot learning? To this end, a comparative study is conducted where 64 students participate in a five-day robot-led training program, while another 73 students receive traditional teacher-led training. Pre/post questionnaires are administered to evaluate students’ engagement levels, and semi-structured interviews are conducted to obtain additional insights. The findings reveal that students with dyslexia are better suited to the interactive and multi-modal features of Kebbi. In contrast, students without dyslexia may prefer the more straightforward features of Minibo, which can still effectively promote engagement and learning. Multi-modal robots can boost engagement and motivation in students with and without dyslexia through novelty and cognitive load management. Emotional connections and interactive elements, such as empathetic and customizable features, enhance engagement and improve learning outcomes.